THE IMPACT OF ACCOUNTING DISCLOSURE OF SOCIAL RESPONSIBILITY ON THE EVALUATION OF THE COMPANY'S SOCIAL PERFORMANCE-AN APPLIED STUDY ON THE SOUTHERN REFINERIES COMPANY / BASRA REFINERY - Saja Ibrahim Abbood; Imad A.S.AL-mashkoor (Scholar Express Journals, 2024)
The aim of the research is to show the effect of accounting disclosure of social activities in the financial statements, and to measure social performance indicators. The researchers relied on the method of separation and quantitative disclosure of social responsibility costs. The research was applied to the Southern Refinery Company as a research sample for the purpose of applying the research. The researchers recommended enacting laws to oblige companies to give priority to social performance and disclose expenses in the financial statements to achieve the goals of social responsibility, and to disclose social performance in the financial statements
Keywords: Corporate social responsibility; accounting disclosure; social performance evaluation